MENINGKATKAN KETERAMPILAN MENULIS, KETERAMPILAN BERKOMUNIKASI LISAN, DAN MOTIVASI BELAJAR SISWA MELALUI PENDEKATAN PROSES MENULIS [IMPROVING WRITING SKILLS, ORAL COMMUNICATION SKILLS, AND STUDENT LEARNING MOTIVATION THROUGH THE WRITING PROCESS APPROACH] - Agnes Murni Zebua (Magister Teknologi Pendidikan Fakultas Ilmu Pendidikan, Universitas Pelita Harapan, 2021)
The writing process approach is used to help students to write more competently through stages of the approach. The design of Static-Group Pretest-Postest is used to investigate the increase on students' writing skills, oral communication skills and learning motivation in Indonesian classes. The subject of the study was 41 Grade 8 students consisting of 21 students in experiment group and 20 students in control group. The study was conducted by implementing the writing process approach as the treatment in experiment class and conventional approach in the control class. The data was analysed using descriptive statistics and Wilcoxon test by comparing the results between pretest and posttest, and Mann Whitney test was used to find the difference between two groups. The findings show that there were increase on writing skills in middle category (N gain =0.48; p =0.000), oral communication skills in middle category (N gain = 0,47; p = 0,000), and learning motivation in low category (N gain = 0,25; p = 0,000) after the implementation of the writing process.